Application Of Poly (3-Hydroxybutyrate-co-3 Hydroxyhexanoate) In Controlled Release Fertilizer For Oil Palm Seedlings - Paramasivam, Murugan (2017)
Polyhydroxyalkanoates (PHAs), a type of biopolymer, are synthesized by various types of bacteria under limited nitrogen source but in the presence of excess carbon source. PHAs are biodegradable and would be a suitable material to replace those non-biodegradable polymers used in controlled release fertilizer (CRF) application. The objectives of this study were to produce poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) [P(3HB-co-3HHx)] coupled with development of biological recovery and purification steps and finally applying the material to develop PHAbased CRF. The biosynthesis of P(3HB-co-3HHx) was studied using feedstock consisting of palm olein (PO) by recombinant C. necator Re2058/pCB113 using shake flask.